Biodiesel production from waste cooking oil: A review - Budiman, Y. (Nova Science Publishers, Inc., 2018)
Waste cooking oil has untapped potentials that can be utilized to produce various useful products. Biodiesel is one of them. Some of the well-known methods to produce biodiesel includes homogeneous acid or base catalyst, bifunctional acid-base catalyst, heterogeneous acid or base catalyst, enzymatic process, supercritical methanol, ultrasound based process, and microwave based process. Some of the on-going works are even a step further into intensifying the process technologies such as the use of reactive distillation and reactive absorption. Some of these processes are in the mature stages, while others are still in their development phase. Typical acid based catalyst suffers from slow reaction rate. On the other hand, the basic catalyst leads to soap formation due to the presence of significant amount of free fatty acids in raw waste cooking oil. Other challenges are to find more efficient separation of the products, simpler process, lower energy consumption, and continuous pilot plant trials for processes that are still in their infancies. This paper outlines some of these developments and the challenges. It discusses also the emerging processes and the process intensification approaches. To this end, there are still plenty of opportunities to improve the process and make it more efficient. Â© 2018 Nova Science Publishers, Inc.